DEEP-WATER RENEWAL IN THE SKAGERRAK DURING THE LAST 1200 YEARS TRIGGERED BY THE NORTH ATLANTIC OSCILLATION: EVIDENCE FROM BENTHIC FORAMINIFERAL δ18O - Brückner S.; Mackensen A. (My University, 2006)
Benthic foraminiferal tests of a sediment core from southwestern Skagerrak (northeastern North Sea, 420 m water depth) were investigated for their ratio of stable oxygen isotopes. During modern times sudden drops in temperature and salinity of Skagerrak deep waters point to advection-induced cascades of colder and denser central North Sea waters entering the Skagerrak. These temperature drops, which are recorded in benthic foraminiferal tests via the stable oxygen isotopic composition, were used to reconstruct deep-water renewal in the Skagerrak. In a second step we will show that, at least during the last 1200 years, Skagerrak deep-water renewal is triggered by the negative phase of the North Atlantic Oscillation (NAO). The NAO exerts a strong influence on the climate of northwestern Europe. It is currently under debate if the long-term variability of the NAO is capable of influencing Northern Hemisphere climate on long timescales. The data presented here cannot reinforce these speculations. Our data show that most of the 'Little Ice Age' was dominated by comparably warm deep-water temperatures. However, we did find extraordinary strong temperature differences between central North Sea waters and North Atlantic water masses during this time interval. © 2006 Edward Arnold (Publishers) Ltd.
Keywords: δ18O; BENTHIC FORAMINIFERA; DEEP-WATER RENEWAL; HOLOCENE; NAO; NORTH SEA; SKAGERRAK; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен